Future Medical Doctors Are Ready to Prescribe Antimicrobials Safely and Rationally - Haque, Mainul (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Therefore, the answer remains in improving clinical pharmacology teaching and learning in undergraduate curriculum [40, 41]with necessary assessment program regarding prescribing skill [40]need to incorporate with the hope situation will improve to provide better health care for common people of this planet.Â 